2021
DOI: 10.3389/fnins.2021.643384
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation in the Rat Anterior Insula and Anterior Cingulate During an Effortful Weightlifting Task

Abstract: When performing tasks, animals must continually assess how much effort is being expended, and gage this against ever-changing physiological states. As effort costs mount, persisting in the task may be unwise. The anterior cingulate cortex (ACC) and the anterior insular cortex are implicated in this process of cost-benefit decision-making, yet their precise contributions toward driving effortful persistence are not well understood. Here we investigated whether electrical stimulation of the ACC or insular cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, lesions to the Cg1 of rats has consistently resulted in avoidance of high-effort options (climbable-barriers, highratio lever presses) when relatively lower effort options are available (45)(46)(47)(48). We have shown previously that electrical stimulation to Cg1 biases rats to quit earlier in our WLT (49).These results seem to be at odds with one another: lesioning Cg1 results in rats shifting their choice preference towards lower effort options, but does not affect high effort performance on progressive ratio tasks. Wang et al (50) provided some clarity on this discrepancy by showing that inactivation of rat Cg1 impairs performance in a novel "do more get more" task, suggesting that Cg1 is critical for self-paced effort expenditure.…”
Section: Discussionmentioning
confidence: 72%
“…However, lesions to the Cg1 of rats has consistently resulted in avoidance of high-effort options (climbable-barriers, highratio lever presses) when relatively lower effort options are available (45)(46)(47)(48). We have shown previously that electrical stimulation to Cg1 biases rats to quit earlier in our WLT (49).These results seem to be at odds with one another: lesioning Cg1 results in rats shifting their choice preference towards lower effort options, but does not affect high effort performance on progressive ratio tasks. Wang et al (50) provided some clarity on this discrepancy by showing that inactivation of rat Cg1 impairs performance in a novel "do more get more" task, suggesting that Cg1 is critical for self-paced effort expenditure.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, to test the specificity of OFC-aIC circuit in compulsive cocaine use, we evaluated whether a gain function of another aIC-related circuit could induce compulsive cocaine use. A previous study found that aIC also received input projections from cingulate cortex area 1 (Cg1) ( 17 , 23 ) (fig. S5), which showed a similar expression of c-Fos between sensitive and resistant rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For chemogenetic regulation of OFC-aIC circuit, AAV 2/1 -hSyn-Cre was bilaterally infused into OFC followed by bilateral infusion of AAV-EF1α-DIO-hM4D(Gi)-mCherry-WPRE-PA, AAV-EF1α-DIO-hM3D(Gq)-mCherry-WPRE-PA, or AAV-EF1α-DIO-mCherry-WPRE-PA in aIC before catheter implantation. For chemogenetic regulation of Cg1-aIC circuit ( 23 ), AAV 2/1 -hSyn-Cre was bilaterally infused in the Cg1 (AP, +3.7; ML, ±0.4; DV, −1.0 mm) followed by bilateral injection of AAV-EF1α-DIO-hM3D(Gq)-mCherry-WPRE-PA or AAV-EF1α-DIO-mCherry-WPRE-PA in aIC before catheter implantation. Moreover, we validated the accuracy of the OFC-aIC and Cg1-aIC labeling (fig.…”
Section: Methodsmentioning
confidence: 99%